Haemodynamic effects of oxytocin versus carbetocin given as intravenous bolus to parturient undergoing caesarean delivery under spinal anaesthesia - Mohd Mahdzir, Fithriah (2014)
Introduction : Postpartum haemorrhage (PPH) is one of the commonest causes of maternal morbidity and mortality. Uterine atony has been showed to be the cause of the most postpartum haemorrhage cases. In 2009 World Health Organization (WHO) in booklet for Prevention of Postpartum Haemorrhage has highly recommended active management of third stage of labour in attempt to reduce the incidence of postpartum haemorrhage by using uterotonic agents like oxytocin or carbetocin as part of active management of third stage of labour is highly recommended to prevent post partum haemorhhage. These medications can affect haemodynamic parameters including reduce in blood pressure and increase in heart rate. Carbetocin is an uterotonic agents licensed to be used in Malaysian Health Ministry since 2011.